Analisis Tingkat Kebugaran Jasmani Siswa Fase C Kelas V Ditinjau Dari Hasil Tes Kebugaran Siswa Indonesia (TKSI) Pada Pembelajaran Jasmani, Olahraga, Dan Kesehatan - Aryan Bayu Aprilyanto; Muhammad alfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the physical fitness level of fifth-grade Phase C students based on the Indonesian Student Fitness Test (Tes Kebugaran Siswa Indonesia/TKSI) in Physical Education, Sports, and Health (PJOK) learning. The study employed a quantitative descriptive research design using a total sampling technique. The participants consisted of 26 fifth-grade students at SDN Percobaan 1, including 16 boys and 10 girls. Data were collected using the Phase C TKSI instrument, which consists of five test items: the Child Ball Test, Move the Ball, Tok Tok Ball Test, the 8 × 10 m Shuttle Run, and the 600-meter Run. The collected data were analyzed using descriptive statistics in the form of frequencies and percentages. The results revealed that the students’ overall physical fitness levels were predominantly in the poor category (34%), followed by moderate (31%), good (22%), very poor (8%), and excellent (5%). Based on gender, male students generally demonstrated physical fitness levels ranging from moderate to good, whereas female students were predominantly classified as moderate to poor. These findings indicate that the physical fitness level of Phase C fifth-grade students remains relatively low, highlighting the need for improvement through more active Physical Education learning, structured exercise programs, and the promotion of healthy lifestyles. The findings are expected to serve as a reference for Physical Education teachers and schools in designing programs to enhance students’ physical fitness.